2015
DOI: 10.1007/s11629-014-3035-z
|View full text |Cite
|
Sign up to set email alerts
|

Clipping alters the response of biomass production to experimental warming: A case study in an alpine meadow on the Tibetan Plateau, China

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Our findings suggested that the response magnitudes of the NDVI, GNDVI, SAVI, AGB and GPP to clipping were stronger than those to experimental warming (Table 1 ). Our previous study, which was conducted in the same alpine meadow sites, also implied that clipping had stronger effects on GPP and AGB in 2012 than did experimental warming 41 . Similarly, clipping had stronger effects on AGB than did experimental warming in an alpine meadow in the Yangtze River Source Region, inland of the Tibetan Plateau 34 .…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Our findings suggested that the response magnitudes of the NDVI, GNDVI, SAVI, AGB and GPP to clipping were stronger than those to experimental warming (Table 1 ). Our previous study, which was conducted in the same alpine meadow sites, also implied that clipping had stronger effects on GPP and AGB in 2012 than did experimental warming 41 . Similarly, clipping had stronger effects on AGB than did experimental warming in an alpine meadow in the Yangtze River Source Region, inland of the Tibetan Plateau 34 .…”
Section: Discussionmentioning
confidence: 79%
“…There were inconsistent interannual variations in growing season precipitation and productivity in the current study. Experimental warming significantly reduced AGB and GPP in 2012 but not 2013, 2014 and 2015 at site A 41 ; significantly reduced GPP in 2013 but not 2012, 2014 and 2015 at site B; and significantly increased the SAVI in 2013 but not 2012, 2014 and 2015 at site C (Figs 1 and 2 ). Likewise, experimental warming did not significantly alter AGB in 1998, but it significantly reduced AGB in 1999–2001 in an alpine meadow at the Haibei station on the Tibetan Plateau 31 .…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…AGB was estimated using a non-destructive approach which was based on a regression equation (AGB = 10.33exp 3.28NDVI , R 2 = 0.64, p < 0.001, n = 135) [47]. …”
Section: Methodsmentioning
confidence: 99%